Glimpses into the life of Al-Ghazali - Abdul Razak, Mohd Abbas; Fatah Yasin, Raudlotul Firdaus (Department of Communication, KIRKHS, IIUM, 2024)
Abu Hamid Muhammad ibn Muhammad al-Ghazali who happened to be a popular figure during the Golden Era of the Muslims is more often known to the world as Imam Al-Ghazali (450H/1058 – 505H/1111). During his time, he was an eminent Muslim jurist, Sufi scholar and thinker. In realizing the great potential of Al-Ghazali, the Seljuk Regime sought his expertise to be their entrusted scholar to repudiate the challenges that came from the philosophers, Batiniyyah, rationalists and others. As a versatile scholar who could debate and reason with his opponents, Al-Ghazali was called Hujjatul Islam (‘authority on Islam’ or ‘proof of Islam’). Although some claimed that he was a philosopher, personally Al-Ghazali chose not to be identified as one, due to the many controversies that surrounded the philosophers of his time, like Al-Kindi (801-873), Al-Farabi (872-950) and Ibn Sina (980-1037).